Complex coastal change in response to autogenic basin infilling: An example from a sub‐tropical Holocene strandplain. Issue 6 (29th April 2016) - Hein, Christopher J.; FitzGerald, Duncan M.; de Souza, Luis H. P.; Georgiou, Ioannis Y.; Buynevich, Ilya V.; Klein, Antonio H. da F.; de Menezes, João Thadeu; Cleary, William J.; Scolaro, Thelma L.
Abstract: Thick bay‐fill sequences that often culminate in strandplain development serve as important sedimentary archives of land–ocean interaction, although distinguishing between internal and external forcings is an ongoing challenge. This study employs sediment cores, ground‐penetrating radar surveys, radiocarbon dates, palaeogeographic reconstructions and hydrodynamic modelling to explore the role of autogenic processes – notably a reduction in wave energy in response to coastal embayment infilling – in coastal evolution and shoreline morphodynamics. Following a regional 2 to 4 m highstand at ca 5·8 ka, the 75 km 2 Tijucas Strandplain in southern Brazil built from fluvial sediments deposited into a semi‐enclosed bay. Holocene regressive deposits are underlain by fluvial sands and a Pleistocene transgressive–regressive sequence, and backed by a highstand barrier‐island. The strandplain is immediately underlain by 5 to 16 m of seaward‐thickening, fluvially derived, Holocene‐age, basin‐fill mud. Several trends are observed from the landward (oldest) to the seaward (youngest) sections of the strandplain: (i) the upper shoreface and foreshore become finer and thinner and shift from sand‐dominated to mud‐dominated; (ii) beachface slopes decrease from >11° to ca 7°; and (iii) progradation rates increase from 0·4 to 1·8 m yr −1 . Hydrodynamic modelling demonstrates a correlation between progressive shoaling of Tijucas Bay driven by sea‐level fall and sediment infilling and a decrease in onshore wave‐energy transport from 18 to 4 kW m −1 . The combination of allogenic (sediment supply, falling relative sea‐level and geology) and autogenic (decrease in wave energy due to bay shoaling) processes drove the development of a regressive system with characteristics that are rare, if not unique, in the Holocene and rock records. These findings demonstrate the complexities in architecture styles of highstand and regressive systems tracts. Furthermore, this article highlights the diverse internal and external processes and feedbacks responsible for the development of these intricate marginal marine sedimentary systems.